1994
DOI: 10.1055/s-2007-1021086
|View full text |Cite
|
Sign up to set email alerts
|

Early Leg Blood Flow Adjustment During Dynamic Foot Plantarflexions in Upright and Supine Body Position

Abstract: The time courses of leg blood flow, systolic peak velocity, heart rate and blood pressure have been studied in nine health volunteers during dynamic exercise in upright sitting and in a tilted sitting body position. In both positions the subjects performed single and repeated foot plantarflexions against light and moderate forces corresponding to 5%-10% and 25%-30% of maximal voluntary contraction. The following measurement techniques were used: Doppler ultrasound method (blood flow parameters), FINAPRES devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
44
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 19 publications
7
44
1
Order By: Relevance
“…Although there is an immediate increase in blood flow to active skeletal muscle with the onset of exercise (1,10,11,15,17,19,20), the mechanism(s) by which this rapid increase in blood flow occurs has remained elusive. The muscle pump theory has been proposed as a rapid, local mechanism by which blood flow to active skeletal muscle can be regulated.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is an immediate increase in blood flow to active skeletal muscle with the onset of exercise (1,10,11,15,17,19,20), the mechanism(s) by which this rapid increase in blood flow occurs has remained elusive. The muscle pump theory has been proposed as a rapid, local mechanism by which blood flow to active skeletal muscle can be regulated.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for this study was that the primary evidence for a muscle pump effect in exercise hyperemia comes from results of experiments which have demonstrated that limb position influences the blood flow response to muscle contraction (12,22,25,31,36). We reasoned that a critical control experiment has been lacking, i.e., testing whether the response to vascular challenges other than contraction elicit positional differences in blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Because of technical limitations, it has not been feasible to perform experiments to directly test this hypothesis, yet the idea has persisted despite the lack of direct confirmation. Data from studies showing a greater blood flow response to muscle contractions when the limb is in the dependent position (12,22,25,31,36) have been the primary evidence for a skeletal muscle pump contribution to exercise hyperemia. We have argued previously that the magnitude of contraction-elicited changes in blood flow is far greater than can be accounted for by putative changes in intravascular pressure (38) and that the time course of changes in blood flow does not correlate with that predicted from the muscle pump (4).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations